Laser-based pretreatment of composite T-joints for improved pull-off strength and toughness. (1st July 2022) - Hashem, M.; Wagih, A.; Lubineau, G.
Abstract: This study demonstrates the efficiency of two CO 2 surface laser treatment strategies for improving the strength and toughness of the adhesive bonding of T-joints. The first strategy involves uniform laser treatment to the surface, and the second strategy involves laser patterning by alternatively applying high- and low-power laser irradiation to the T-joint stiffener and skin surfaces. All the laser-treated T-joints showed progressive failure modes during pull-off test, unlike the PP surface-treated joints that exhibited brittle failure. The uniform laser-treated joints exhibited improved strength and toughness because contaminants were removed and the fibers were exposed to be directly bonded with adhesive. The joints subjected to the laser-patterning strategy demonstrated a substantial improvement in terms of the strength and toughness, reaching values of 2.2 and 12 times those of the PP surface-treated T-joints, respectively. This is because of the crack arresting at the transition between the two treatments at the stiffener interface, inducing crack migration from the stiffener–adhesive interface to the skin–adhesive interface while forming adhesive ligaments. The formation, deformation, and breakage of these ligaments dissipated more energy, hence increasing the effective joint toughness and strength.